Reproductive performances of wild male tiger shrimp Penaeus monodon post-injection of oocyte developer without eyestalk ablation - Dony Prasetyo; Asda Laining; Agus Oman Sudrajat (Jurnal Akuakultur Indonesia)
ABSTRACT